Exceptional aerobic scope and cardiovascular performance of pink salmon ( Oncorhynchus gorbuscha ) may underlie resilience in a warming climate - Clark, Timothy D.; Jeffries, Kenneth M.; Hinch, Scott G.; Farrell, Anthony P. (Journal of experimental biology, 2011)
Little is known of the physiological mechanisms underlying the effects of climate change on animals, yet it is clear that some species appear more resilient than others. As pink salmon (Oncorhynchus gorbuscha) in British Columbia, Canada, have flourished in the current era of climate warming in contrast to other Pacific salmonids in the same watershed, this study investigated whether the continuing success of pink salmon may be linked with exceptional cardiorespiratory adaptations and thermal tolerance of adult fish during their spawning migration. Sex-specific differences existed in minimum and maximum oxygen consumption rates ( and , respectively) across the temperature range of 8 to 28°C, reflected in a higher aerobic scope () for males. Nevertheless, the aerobic scope of both sexes was optimal at 21°C (Topt) and was elevated across the entire temperature range in comparison with other Pacific salmonids. As Topt for aerobic scope of this pink salmon population is higher than in other Pacific salmonids, and historic river temperature data reveal that this population rarely encounters temperatures exceeding Topt, these findings offer a physiological explanation for the continuing success of this species throughout the current climate-warming period. Despite this, declining cardiac output was evident above 17°C, and maximum attainable swimming speed was impaired above ∼23°C, suggesting negative implications under prolonged thermal exposure. While forecasted summer river temperatures over the next century are likely to negatively impact all Pacific salmonids, we suggest that the cardiorespiratory capacity of pink salmon may confer a selective advantage over other species.